Composite materials based on metal-organic frameworks loaded with effective therapeutic components for promoting wound healing - Wang, Shaogeng; Huang, Fuchao; Wang, Junbo; Wu, Xiaomin; Pan, Xiaohua (Frontiers in Materials, 2026)
Wound repair has long been a challenging area in medical research and clinical treatment. The unique properties of MOFs(metal organic frameworks), including their highly tunable porous structures, significant specific surface area, and ease of functionalization, make them particularly useful for drug delivery applications. MOFs can efficiently load a variety of therapeutic agents, such as small molecule drugs, biomolecules, gas molecules, nanoparticles, and photosensitizers, enabling slow, controlled release and precise, targeted delivery of these substances. Moreover, MOFs can be combined with other materials to create multifunctional wound dressings. This review introduces the mechanisms and advantages of MOFs loaded with therapeutic agents and provides an overview of the latest research progress in composite materials based on MOFs loaded with effective therapeutic components for wound treatment.